Finger Cue for Mobile Robot Motion Control - Tresna Dewi; Amperawan Amperawan; Pola Risma; Yurni Oktarina; Dicky Astra Yudha (Universitas Sriwijaya, 2020)
The current technology enables automation using a robot to help or substitute humans in industry and domestic applications. This robot invasion to human life emerges a new requirement to set a method of communication between a human and a robot. One of the oldest languages is finger gesture, and this is easy to be applied method by implementing image detection that connected to the actuators of the robot to respond to human orders. This paper presents a method to navigate robots based on human fingers cue, including